2001
DOI: 10.1038/sj.cdd.4400796
|View full text |Cite
|
Sign up to set email alerts
|

Staurosporine-induced apoptosis of HPV positive and negative human cervical cancer cells from different points in the cell cycle

Abstract: In the present study, we compare the sensitivity of CaSki and HeLa cells (HPV positive, wild-type p53) and C33A cells (HPV negative, mutated p53) to a protein kinase inhibitor, the staurosporine (ST). We show that ST can reversibly arrest the three cervical-derived cell lines, either in G1 or in G2/M. Beyond certain ST concentrations or/and over 24 h exposure, the cells underwent apoptosis. This process took place in G1 and G2/M for C33A and CaSki plus HeLa cell lines, respectively. By using an in vitro cell-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 55 publications
4
32
0
1
Order By: Relevance
“…Bernard et al showed that the p53 activity might involve in the apoptotic susceptibility of HPV infected cells when they compared the HPV-positive cells containing wild type p53 with the HPV-negative cells containing mutated p53 [15]. Our results here demonstrated that the cell-cycle dependent apoptosis was related with the differential transregulation of p53 on the basis of the silencing of E6 and restoration of functional p53.…”
Section: Profiling Of Genes Differentially Expressed Between Early-s supporting
confidence: 58%
See 1 more Smart Citation
“…Bernard et al showed that the p53 activity might involve in the apoptotic susceptibility of HPV infected cells when they compared the HPV-positive cells containing wild type p53 with the HPV-negative cells containing mutated p53 [15]. Our results here demonstrated that the cell-cycle dependent apoptosis was related with the differential transregulation of p53 on the basis of the silencing of E6 and restoration of functional p53.…”
Section: Profiling Of Genes Differentially Expressed Between Early-s supporting
confidence: 58%
“…It was reported that cells treated with some antitumor agents had different susceptibility to apoptosis in a cell cycle related manner [14]. This cell cycle stage-dependent susceptibility to apoptosis was also found in cells treated with staurosporine [15] and arsenite [16]. This different susceptibility may be explained by the variety of the lesion severity and the repair ability to the lesion.…”
Section: Introductionmentioning
confidence: 84%
“…Indeed, our ST treatment on CaSki and HeLa cells induced the proteolytic cleavage of 116 kDa PARP protein to yield the characteristic 85 kDa fragment. Finally, typical morphological changes have been observed in our apoptotic HPV-positive cancer cells, and previously described in detail (Bernard et al, 2001). …”
Section: Discussionmentioning
confidence: 87%
“…Recently, we have demonstrated that staurosporine (ST), an inhibitor of multiple protein kinases, induces apoptosis of CaSki and HeLa cells, which specifically appears from the G2/M cycle phase (Bernard et al, 2001). However, the mechanisms by which ST activates the apoptotic cascade are not well understood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation